Comparative education the construction of a field - Manzon, Maria (CERC studies in comparative education, 2011)
At the beginning of the 21st century, new features have emerged within the field of comparative education. Some of these features result from new technologies, while others reflect political transitions and the forces of globalisation. The field embraces new insights on cultures, and scholars are exploring diverse units of analysis. This book presents perspectives on these changes while noting various continuing traditions. Its contributors come from a wide range of countries and contexts, and present their work within a framework set by the 11th congress of the World Council of Comparative Education Societies (WCCES). The book makes a valuable methodological as well as a conceptual contribution to the field.